2021
DOI: 10.1101/2021.08.23.457229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA Vaccination Induces Durable Immune Memory to SARS-CoV-2 with Continued Evolution to Variants of Concern

Abstract: SARS-CoV-2 mRNA vaccines have shown remarkable efficacy, especially in preventing severe illness and hospitalization. However, the emergence of several variants of concern and reports of declining antibody levels have raised uncertainty about the durability of immune memory following vaccination. In this study, we longitudinally profiled both antibody and cellular immune responses in SARS-CoV-2 naive and recovered individuals from pre-vaccine baseline to 6 months post-mRNA vaccination. Antibody and neutralizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
13

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 57 publications
(61 reference statements)
4
47
0
13
Order By: Relevance
“…This higher level of antibody after the booster injection compared to the second injection is indicative of a robust immune memory response likely due to stimulation of memory B cells. [30][31][32][33] It is also important to note that the results here using a validated pseudovirus neutralization assay showed that the GMTs after the second dose of mRNA-1273 were higher at one month after the second dose in the 100 µg group (1268.0; 95% CI=1087.9, 1477.8) compared to the 50 µg group (629.2; 549.3, 720.8) (Figure 3; Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 84%
“…This higher level of antibody after the booster injection compared to the second injection is indicative of a robust immune memory response likely due to stimulation of memory B cells. [30][31][32][33] It is also important to note that the results here using a validated pseudovirus neutralization assay showed that the GMTs after the second dose of mRNA-1273 were higher at one month after the second dose in the 100 µg group (1268.0; 95% CI=1087.9, 1477.8) compared to the 50 µg group (629.2; 549.3, 720.8) (Figure 3; Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 84%
“…It suggested that the cellular response weakens through the time as it was raised by epidemiologic and immunological studies. [27][28][29][30] In conclusion our work shows that humoral immune response to SARS-CoV-2 vaccine is severely impaired in patients treated with Rituximab and Ibrutinib. Significant fraction of these patient mounts cellular immune response to the vaccine.…”
Section: It Has Indeed Been Shown That Ibrutinib Restores T Cell Number and Function In Cll Patientsmentioning
confidence: 98%
“…From an immunological standpoint, plasma neutralising antibody titres are expected to decay eventually following vaccination, but robust and long lived plasmablast and germinal B cell responses have been shown after mRNA vaccination, and memory B cells have been shown to increase over at least six months, improve functionally, and provide cross-variant protection 1213. Plasma neutralising antibody titres may predict some level of protection from symptomatic infection.…”
Section: Long Term Immune Responsementioning
confidence: 99%
“…Most importantly, the long term effect of boosters on reducing infection, transmission, and hospital admissions remains unknown. Although boosters increase plasma antibody levels and may temporarily extend antibody mediated protection, they have not been shown to augment the memory B and T cell responses expected to provide long term protection against severe disease for most immunocompetent people 16. In an observational study from Israel reporting benefit associated with a third dose of the Pfizer-BioNTech vaccine (BNT162b2),17 the follow-up period in the boosted group was just seven person days for severe disease and 12 person days for infection—too short to assess long term effectiveness.…”
Section: Long Term Immune Responsementioning
confidence: 99%